Imported inputs and the countercyclicality of net exports in emerging markets - Suleyman Tolga Tiryaki (Central Bank Review (CBR), 2019)
This paper shows that the strong countercyclicality of net exports observed in emerging market economies can be explained to a large extent by the use of imported inputs in production. We build a single-sector small open economy business cycle model featuring imported inputs and variable capital utilization in production, and a working capital constraint. The model yields countercyclical net exports and realistic business cycle dynamics. The magnitude of the countercyclicality of net exports increases with the share of imported inputs. The elasticity of substitution between domestic and imported inputs is also critical in obtaining this result. The model also attributes an important role to import prices in matching the business cycle facts in emerging markets.
Keywords: 330; Business cycles; Emerging markets; Imported inputs; Countercyclical net exports